Common flaws in library and information sciences (LIS) PhD theses submitted for examination in east, southern and west African universities - Mutula, Stephen; Majinge, Rebecca M. (Qualitative and Quantitative Methods in Libraries, 2019)
The successful completion of a thesis is a requirement for the award of doctoral degree (PhD) in the information sciences in east, southern and west African universities. This article is aimed at presenting the experiential views of the authors on the common flaws found in library and information sciences (LIS) PhD theses submitted for examination in 15 purposively selected universities in Kenya, Uganda, Botswana, Ghana, and South Africa. The results revealed several flaws such as poor writing skills, failure to apply theory as a framework to organise content; generate research questions; guide literature review; and discuss the findings. Furthermore, the candidates fail to link the findings with the research questions and the technical presentation of citations in the text and list of references is a major challenge. These flaws may be attributed to a number of factors such as inadequate preparedness and limited skills and competencies on the part of supervisors and the candidates; the limited support in the form of workshops given to PhD to improve their writing; absence of course work as part of the PhD programmes and masters programmes. The authors recommend capacity building programmes to improve writing and supervision of PhD theses. A rethinking of the LIS PhD model from the current research based to a more hybrid model is recommended.